2020
DOI: 10.1371/journal.pone.0239902
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department patients with weakness or fatigue: Can physicians predict their outcomes at the front door? A prospective observational study

Abstract: Background Generalized weakness and fatigue are underexplored symptoms in emergency medicine. Triage tools often underestimate patients presenting to the emergency department (ED) with these nonspecific symptoms (Nemec et al., 2010). At the same time, physicians’ disease severity rating (DSR) on a scale from 0 (not sick at all) to 10 (extremely sick) predicts key outcomes in ED patients (Beglinger et al., 2015; Rohacek et al., 2015). Our goals were (1) to characterize ED patients with weakness and/or fatigue (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…17 Several studies have investigated physician assessment of mortality risk in patients admitted to the ED. Herzog et al 40 reported accurate physician prediction of mortality in patients admitted with generalized weakness and fatigue. Similarly, Zelis et al 20 found that clinical intuition documented at admission could predict mortality and other adverse outcomes in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several studies have investigated physician assessment of mortality risk in patients admitted to the ED. Herzog et al 40 reported accurate physician prediction of mortality in patients admitted with generalized weakness and fatigue. Similarly, Zelis et al 20 found that clinical intuition documented at admission could predict mortality and other adverse outcomes in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between fatigue and hospitalization risk is also consistent in the literature for numerous disease processes. Herzog et al 92 found that weakness and/ or fatigue can predict hospitalization and transfer to intensive care units in patients assessed in the emergency department setting regardless of disease process. Thus, fatigue may be an indicator of disease severity and a predictor of patient outcomes and should therefore be addressed as a priority symptom.…”
Section: Discussionmentioning
confidence: 99%
“…This has been concluded in other investigations. For example, Herzog, Jenny, Nickel, Nieves-Ortega, and Bingisser. (2020) found that a physician's "impression" of acute morbidity and mortality in patients presenting to the ED with generalized weakness and fatigue accurately predicted mortality, hospitalization, and transfer to the intensive care unit.…”
Section: Author's Discussionmentioning
confidence: 99%